Evaluation of Particle Size and Friction Coefficients in Sintered Metal Process Development by Discrete Element Simulation - Naoki Yashiro; Natsuko Sugimura; Hitoshi Washizu (Tribology Online)
The effects of particle size and friction coefficients of Fe-Ni-Mo steel powder on their filling behavior by a discrete element method (DEM) simulation were investigated. Our original DEM code based on FDPS (Framework for Developing Particle Simulator) was used for these simulations. First, the difference between the experimental and simulated values of the apparent density (simulation error) depends on the particle size, and in this case, the minimum level (＜10%) was reached when the particle size was 300-500 μm. In addition, the simulation with a 500 μm particle size model were found to yield an equivalent simulation accuracy in 1/5 the computation time of the 300 μm model. Next, the additives-induced decreases in the friction coefficients were applied to the simulation. In the experiment, the additives increased the apparent density by 6.7%, whereas in the simulation, it increased by 7.1%, showing that the differences in the friction coefficients can be qualitatively and quantitatively reproduced in the simulation. These results indicated that this simulation method can contribute to increasing the efficiency and speed of materials and manufacturing process development of sintered metal products.